Analisis Pengaruh Bangunan Shelter Loading Ramp Terhadap Kenaikan Free Fatty Acid (FFA) TBS di Perkebunan Kelapa Sawit: Analysis of The Effect of Shelter Loading Ramp Buildings on The Increase of Free Fatty Acids (FFA) in Fresh Fruit Bunches (FFB) at Oil Palm Plantations - Sri Ngapiyatun; Prudencia Cinta Devicha; Pandhu Rochman Suosa Putra; Wartomo; Humairo Aziza; Ahmad Zamroni; Rusli Anwar (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2026)
Crude Palm Oil (CPO) is a key commodity playing a vital role in meeting global demands across the food, oleochemical, and renewable energy industries. A primary quality parameter for CPO is its free fatty acid (FFA) content. FFA levels are influenced by lipolytic enzyme activity, high temperatures, humidity, and exposure to air during handling and storage. This study aimed to examine how the design and operational conditions of loading ramp shelters specifically contribute to changes in the FFA levels of Fresh Fruit Bunches (FFB), which in turn affect the quality of the final CPO product. In this study, FFB were placed at three locations: an outdoor area (P1), an outdoor area with water spraying (P2), and a shelter (P3), and their FFA content was analyzed after 1 to 7 days of post-harvest storage. The results showed that the lowest increase in FFA levels occurred with the shelter treatment (P3), as it was more effective at suppressing FFA accumulation, particularly during rainy weather.